Effects of student pairing and public review on physical activity during school recess. Issue 3 (17th April 2017) - Zerger, Heather M.; Miller, Bryon G.; Valbuena, Diego; Miltenberger, Raymond G.
Abstract : The purpose of this study was to evaluate the effects of student pairing and feedback during recess on children's step counts. During baseline, participants wore a sealed pedometer during recess. During intervention, we paired participants with higher step counts with participants with lower step counts. We encouraged teams to compete for the highest step count each day and provided feedback on their performance during each recess session. Results showed a large mean increase in step count from baseline to intervention. These results suggest that children's steps during recess can be increased with a simple and cost‐effective intervention.